2019
DOI: 10.26434/chemrxiv.9745388.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Epoxide Intermediate in Glycosidase Catalysis

Abstract: <div>Retaining glycoside hydrolases cleave their substrates through stereochemical retention at the anomeric position. Typically, this involves two-step mechanisms using either an enzymatic nucleophile via a covalent glycosyl enzyme intermediate, or neighboring group participation by a substrate-borne 2-acetamido neighboring group via an oxazoline intermediate; no enzymatic mechanism with participation of the sugar 2-hydroxyl has been reported. Here, we detail structural, computational and kinetic eviden… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…The catalytic efficiency is similar to that displayed by BtGH99 on the epimeric Man4OMe substrate (KM = 2.6 mM, kcat = 180 min -1 , kcat/KM = 69 mM -1 min -1 ) (31). The E404Q variant of MANEA-Δ97 was inactive on this substrate, consistent with the proposed mechanism (35).…”
Section: Treatment Of Glcman9glcnac2 With Recombinant Manea-δ97 Releasupporting
confidence: 77%
“…The catalytic efficiency is similar to that displayed by BtGH99 on the epimeric Man4OMe substrate (KM = 2.6 mM, kcat = 180 min -1 , kcat/KM = 69 mM -1 min -1 ) (31). The E404Q variant of MANEA-Δ97 was inactive on this substrate, consistent with the proposed mechanism (35).…”
Section: Treatment Of Glcman9glcnac2 With Recombinant Manea-δ97 Releasupporting
confidence: 77%
“…35 Broadly, glycosidases operate at intermediate pH ranges and utilize general catalysis to assist substitution reactions at the anomeric center by water or an enzymatic nucleophile (exceptions occur for outstanding leaving groups such as fluoride and 2,4-dinitrophenolate). 35 However, a mechanism involving neighboring group participation by the 2hydroxyl of an α-mannoside (also likely benefiting from general base catalysis) has been demonstrated for a bacterial endo-α-1,2-mannosidase, 36 which shares obvious similarities to that studied here.…”
Section: Discussionmentioning
confidence: 99%
“…[5] In sharp contrast, aziridine derivatives tend to react faster in enzymatic media, such as in the active sites of glycoside hydrolases, as the NH-group is primed for attack by protonation, [3] with some exceptions. [6] Significantly less is known about the reactivity of phosphiranes and thiiranes, while it has been suggested that thiiranes are more reactive than epoxides. [7] A deeper understanding of the chemistry of nucleophilic ring-opening reactions of these strained three-membered ring systems can guide the design of these irreversible enzyme inhibitors and probes.…”
Section: Introductionmentioning
confidence: 99%